Technology acquisition by enterprises - a comparison between technology self-making and buying - Tuyen, Hoang Van (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Any enterprise, especially productive/manufacturing enterprises, must use at least one technology to develop and maintain its competitive advantage. Technology used in enterprises was acquired through various different modalities. However, each enterprise has different decision in the selection of appropriate modality to acquire technology, whether to create technology at the enterprise by themselves 1 or receive it from outside or take combined action. This article attempts to provide an overview on different modalities being utilized by enterprises to acquire technology, compare the strengths and weaknesses of each modality. Code: 14110601